A new look at old friends – I. Imaging classical radio galaxies with uGMRT and MeerKAT. Issue 4 (31st May 2021) - Fanaroff, Bernie; Lal, Dharam V; Venturi, Tiziana; Smirnov, Oleg M; Bondi, Marco; Thorat, Kshitij; Bester, Landman H; Józsa, Gyula I G; Kleiner, Dane; Loi, Francesca; Makhathini, Sphesihle; White, Sarah V
ABSTRACT: We have undertaken a systematic study of FR I and FR II radio galaxies with the upgraded Giant Metrewave Radio Telescope (uGMRT) and MeerKAT. The main goal is to explore whether the unprecedented few μJy sensitivity reached in the range 550–1712 MHz at the resolution of ∼4–7 arcsec reveals new features in the radio emission which might need us to revise our current classification scheme for classical radio galaxies. In this paper, we present the results for the first set of four radio galaxies, i.e. 4C 12.02, 4C 12.03, CGCG 044–046, and CGCG 021–063. The sources have been selected from the 4C sample with well-defined criteria and have been imaged with the uGMRT in the range 550–850 MHz (band 4) and with the MeerKAT in the range 856–1712 MHz ( L -band). Full resolution images are presented for all sources in the sample, together with MeerKAT in-band spectral images. Additionally, the uGMRT–MeerKAT spectral image and MeerKAT L -band polarization structure are provided for CGCG 044–046. Our images contain a wealth of morphological details, such as filamentary structure in the emission from the lobes, radio emission beyond the hotspots in three sources, and misalignments. We briefly discuss the overall properties of CGCG 044–046 in the light of the local environment as well, and show possible restarted activity in 4C 12.03 which needs to be confirmed. We conclude that at least for the sources presented here, the classical FR I/FR II morphological classification still holds with the current improved imaging capabilities, but the richness in details also suggests caution in the systematic morphological classification carried out with automatic procedures in surveys with poorer sensitivity and angular resolution.